Design and development of indoor device for recycling of domestic vegetable scrap - Harshitha, Jampala (Environmental technology, 2016)
Since the municipal waste management and community garbage-treating systems are in vogue, there is a growing need for the waste minimization to keep our vicinity clean and green. Therefore, a feasible indoor device is designed for recycling domestic vegetable scrap by adopting the principle of soil ecosystem. To arrive at the composting process control parameters in the proposed device, the soil from landfill and quarry along with supplements namely sawdust, cow dung/yeast and the resident thermophilic bacteria are analysed. The soil parameters namely pH, electrical conductivity, Organic carbon, P, K, Fe, moisture content and the presence of thermophilic bacteria varied significantly between negative control sample (NCS) and positive control sample (PCS) and post-treatment positive control group with dried cow dung (PPC-C)-derived compost is soft-textured and homogenous. Furthermore, the double-compartment-based device would be more feasible and appealing as a recycling bin rather than as a refuse storage bin primarily due to the inclusion of dish-plantation. The standardization of composting control parameters is discussed in this article